Mulching effect on water management in agro-ecological systems: a review - T. N. Shaikh; Janki R. Patel; B. H. Patel (Aqua, 2023)
The rapidly growing world population, inadequate accessible freshwater resources, and frequent erratic changes in climate have stressed human beings and compelled them to take vital initiatives to prevent water wastage. Water conservation efforts are also intensified in the world's largest water-consuming agriculture sector. The water use efficiency in agronomy has already been enhanced by the adoption of the drip irrigation method, intended to supply water directly to the crop, rather than the land around, thereby minimising water losses up to 70% occurring through evaporation and distribution. Mulching in association with drip irrigation in arid crop agronomy leads to mitigating vigorously water stress in agriculture. Mulch is a layer of natural or synthetic or combination material applied to the surface of the soil as a protective medium between the soil and the atmosphere. Entirely, it is an efficient medium for soil moisture conservation, and soil temperature control, adds nutrients to the soil by preventing leaching and more efficient use of fertilisers, resistor to erosion losses, suppressing the weeding and improving the visual look of landscapes. This review paper covers various aspects of mulch, emerging as a dynamic water and soil management tool without affecting the value of crops in agriculture. HIGHLIGHTS The rapidly growing world population, inadequate accessible freshwater resources, and frequent changes in climate have stressed human beings and compelled them to take vital initiatives to prevent undue wastage of water.; This covers various aspects of mulch, emerging as a dynamic water and soil management tool without affecting the value of crops in agriculture.;